2022
DOI: 10.1088/1748-605x/aca133
|View full text |Cite|
|
Sign up to set email alerts
|

3D biodegradable shape changing composite scaffold with programmable porous structures for bone engineering

Abstract: This study developed a biodegradable composite porous polyurethane scaffold based on polycaprolactone and polyethylene glycol by sequential in-situ foaming salt leaching and freeze-drying process with responsive shape changing performance. Biomineral hydroxyapatite (HA) was introduced into the polyurethane matrix as inorganic fillers. Infrared spectroscopy results proved a successful synthesis, scanning electron microscopy showed that the scaffold’s porosity decreased with the addition of HA while the average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The hydrogel's sol phase at room temperature is highly injectable, offering significant advantages for minimally invasive procedures. As depicted in figure 2(b), the hydrogel smoothly passes through needles of various gauges (16,18, and 21 G), enabling precise delivery to targeted areas within the body. This property obviates the need for extensive incisions, thereby streamlining surgical interventions.…”
Section: Thermoresponsive Hydrogel Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrogel's sol phase at room temperature is highly injectable, offering significant advantages for minimally invasive procedures. As depicted in figure 2(b), the hydrogel smoothly passes through needles of various gauges (16,18, and 21 G), enabling precise delivery to targeted areas within the body. This property obviates the need for extensive incisions, thereby streamlining surgical interventions.…”
Section: Thermoresponsive Hydrogel Synthesismentioning
confidence: 99%
“…HA incorporation in a composite biomaterial as a reinforcement notably improved its mechanical properties [14][15][16][17]. Incorporating HA and calcium phosphate as inorganic fillers in polyurethane scaffolds enhances their shape memory performance, mechanical properties, and osteoconductivity [18,19]. CS HGs demonstrated good osteoblast adhesion and remarkable potential for tissue regeneration applications [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…It is also necessary to determine the recovery time. For this purpose, the time taken by a sample with a temporary shape to return to its permanent shape under the given stimulus is measured. For example, Kang et al fabricated a thermally induced biobased poly­(butanediol/isosorbide/sebacate/itaconate) (PBISI) SMP. It exhibited elastomeric behavior above its T m and was deformed into a temporary shape.…”
Section: Quantification Of Shape Memory Efficiencymentioning
confidence: 99%
“…[38] Studies have shown that the introduction of HA can enhance the mechanical properties and osteocompatibility of PUA simultaneously. [39] In this study, the influences of HA content on the mechanical properties of adhesive materials have been investigated through compression tests (Figure 3e). As shown in Figure 3f,g and Figure S4b (Supporting Information), the compressive strength and compressive modulus increased with the increase of the HA contents, up to 6 wt% HA followed by a sudden decrease.…”
Section: Preparation and Characterization Of Pu Bone Adhesivesmentioning
confidence: 99%